MOBILE MULTI-POSITION AIR-NAVIGATION-LANDING SYSTEM AND ITS PARAMETERS IN LANDING MODE - Petrova, Yuliia; Osipchuk, Alina; Fialkina, Tetiana (Proceedings of National Aviation University (archive), 2020)
The structure of the navigation and landing system for light-weight aviation tasks, its operation principle, potential technical parameters, and the configuration of the airborne and ground-based equipment are proposed in the article. The operating modes of the system airborne equipment and its communication and interaction with standard aircraft instruments have been developed. Based on the tactics of using such system, the parameters of its frequency-code channels and the principles of its controlling are determined, which allow to identify the multi-position components of its ground-based equipment. The ways to improve system characteristics are proposed. An analysis of the aircraft location determination errors for a mobile two-position radio rangefinder ground-based inquiry-response system is carried out. The possibility of providing a categorized landing of light aircrafts in the signal field of such system is shown.